A Defense of the Demonstration of Order of Thomas Aquinas and William Paley (with Emphasizing Javadi Amoli’s Opinions) - Farah Ramin (آموزه‌‌های فلسفه اسلامي, 2022)
Thomas Aquinas’s purposeful argument and William Paley’s watchmaker argument are the two prominent types of analogical commentaries that confront serious critiques. This research to answer these questions has been arranged: what is the difference between Aquinas’s argument and Paley’s one? Are the analogical speeches able to prove the existence of God? By applying the analytical-critical method these outcomes are achieved: Paley’s argument is based on the spatial order and the structure of living things and the argument of Thomas based on temporal order and their functioning. Both arguments can be thought the samples of likeness (similitudo) of the analogical (similitude), approving arguments of order. Analogy or likeness has been applied in three positions: definition, approval (affirmation) and reasoning. According to Javadi Amoli’s opinions, as well analogical (tamthili) commentaries are useful in the position of definition and the best debate in the position of approval it is counted a piece of a strict evidence for the existence of God, too. The sacred books such as the holy Quran and tradition prove this obvious matter. In this position according to the principle of the congruity of cause and effect, the ordered effect originates from the All-Wise and All-Knower cause and the basis of similarity between things natural and human (man-made things and natural things) is not only analogy. From his point, the argument of Thomas is arranged in accordance with the objective system which is in the chain of purposes (goals) ends to the last purpose.